Proceedings of the 2025 6th International Conference on Big Data and Social Sciences (ICBDSS 2025) - Norjihan Binti Abdul Ghani; Nik Zulkarnaen Khidzir; Hongbo Li; Muath Obaidat (Atlantis Press International BV, 2026)
This is an open access book. As a leading role in the global megatrend of scientific innovation, China has been creating a more and more open environment for scientific innovation, increasing the depth and breadth of academic cooperation, and building a community of innovation that benefits all. Such endeavors are making new contributions to the globalization and creating a community of shared future. 2025 6th International Conference on Big Data and Social Sciences (ICBDSS 2025) will be held on October 24 - 26, 2025, in Jeju Island, Korea. In order to allow more scholars to have the opportunity to participate in the conference to share and exchange experience. This conference mainly focused on'big data','social science'and other research fields to discuss. At present, my country has entered the era of'big data cloud migration', that is, the era of big data, the Internet of things, cloud computing and mobile Internet. The market demand for big data talents is also increasing day by day. The purpose of the conference is to provide a way for experts, scholars, engineering technicians, and technical R&D personnel engaged in big data and social science research to share scientific research results and cutting-edge technologies, understand academic development trends, broaden research ideas, strengthen academic research and discussion, and promote the academic achievement industry Platform for chemical cooperation. The conference sincerely invites experts, scholars from domestic and foreign universities, scientific research institutions, business people and other relevant personnel to participate in the conference.